2012
DOI: 10.1002/mop.27253
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable wide slot antenna integrated with sirs for UWB/multiband communication applications

Abstract: A reconfigurable wide slot antenna integrated with stepped impedance resonators (SIRs) and ideal switches for ultra‐wideband (UWB) and multiband communication applications is proposed. The proposed reconfigurable antenna can be used as a UWB antenna, a dual notch‐band UWB antenna, and multiband antennas. The dual notch‐band functions are obtained by using two stepped impedance stub‐loaded SIRs. The reconfigurable characteristics are achieved by using two ideal switches on SIRs. The measurement and simulation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 13 publications
(15 reference statements)
0
36
0
Order By: Relevance
“…However, this interference could be minimized by creating notched response at these frequency bands. Notch structure could be realized by inserting U-shaped, C-shaped, -shaped slot, stepped impedance stub (SIS), stepped impedance resonators (SIR), SIS loaded hexagon stepped impedance resonators (HSIR), rectangular split ring, defected microstrip structure band stop filter (DMS-BSF), open ended T-shaped stub, etching spur slot, and half and quarter-wavelength strip in the form of resonator, either in the ground plane or in radiating plane itself [10][11][12][13], [15][16][17][18][19][20]. In most of these works, authors have reported reconfigurable UWB operation with single notch or multiple notches.…”
Section: Introductionmentioning
confidence: 99%
“…However, this interference could be minimized by creating notched response at these frequency bands. Notch structure could be realized by inserting U-shaped, C-shaped, -shaped slot, stepped impedance stub (SIS), stepped impedance resonators (SIR), SIS loaded hexagon stepped impedance resonators (HSIR), rectangular split ring, defected microstrip structure band stop filter (DMS-BSF), open ended T-shaped stub, etching spur slot, and half and quarter-wavelength strip in the form of resonator, either in the ground plane or in radiating plane itself [10][11][12][13], [15][16][17][18][19][20]. In most of these works, authors have reported reconfigurable UWB operation with single notch or multiple notches.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency reconfiguration usually consists in translating the operating band [2], creating new bands [3][4][5], but an important proportion of them consists in switching between a wideband mode and one of its sub-bands [6][7][8][9]. This last category of reconfigurable antennas is of particular interest for the proposed context as they allow varying the operating bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report that permitted the commercial operation of ultra wideband (UWB) adopted by FCC (The Federal Communications Commission of the United States) in 2002 [1], many researchers have developed several antenna designs to enhance the impedance bandwidth of small antennas, to make it suitable for UWB applications [2][3][4][5][6]. Recently, the UWB technology has been regarded as one of the most promising wireless technologies that allows the revolutionizing highdata transmission rate and enables the personal area networking industry leading to new innovations and greater quality of services for mobile users [7].…”
Section: Introductionmentioning
confidence: 99%